Mixed methods single case study research (MMSCR): Challenges in WP evaluation. (1st July 2020) - Zivtins, Roberts; Jay, Tim; Winston, Robert; Alexander, Annalisa
Evaluating widening participation (WP) interventions is complex. Early efforts at WP evaluation were criticised for lacking rigour. These criticisms were accompanied with suggested approaches to research, typically favouring randomised control trials. Yet these recommendations have, in turn, become the focus of much discussion and debate within the WP evaluation sector; This paper presents the use of a 'mixed methods single case study research' (MMSCR) study design to WP evaluation. It describes the work of a PhD researcher evaluating the school – university partnership science outreach programme between the Wohl Reach Out Lab at Imperial College London and a local secondary school; The article highlights potential challenges when using MMSCR, namely in ensuring internal validity and trustworthiness of the study. Solutions to these challenges are presented and the case is made for broadening what is seen as meaningful research in the sector.